MICROALBUMINURIA ON DIABETES PATIENTS MELLITUS TYPE 2 HYPERTENSIVE - Evy Yulianti (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2009)
Diabetes mellitus (DM) is a metabolic aberration that can cause some complications, including the occurrence of diabetic nephrophaty (DN). Patients with type 2 DM usually have hypertension likely to double compared to the non-DM patients. Prevalence of hypertension is usually greater in patients with type 2 DM with increased albumin in their urine. Data estimate that microalbuminuria is a value as the index of vaskuler damage, especially in the DM and hypertension. The objective of this research is to investigate microalbumin in type 2 DM patients normotensif and type 2 DM patients hypertensif and assess the influence of blood pressure as risk factors in the occurrence of DN in type 2 DM patients. Subjects of this study are 87 people with type 2 DM normotensif and hipertensif consisting of 54 ND patients and 33 non ND. Microalbumin is measured with the dipstick microalbumin and blood pressure with a sphygmomanometer. The comparison between the control group who examined was showed with X2 with two degrees of freedom with significance level (alpha) 0.05 and odds ratio calculation is done. Results obtained in this research is people with type 2 DM hypertensif have a higher frequency in the DN group (67.3%) compared to the non-DN (p = 0.043) with OR = 2.64. Conclusion of this research is the positive result of the microalbumin examination is bigger in the people with type 2 DM hypertensif and hypertension is a risk factor for occurrence of ND in type 2 DM patients